NUMERACY MANIPULATING SKILLS AS A SUSTENANCE OF NATIONAL DEVELOPMENT IN NORTH-CENTRAL, NIGERIA - Akanmu, Makanmu (Journal of Arts & Social Sciences, 2022)
Education is an instrument used to empower an individual to become a useful member of society through the acquisition of basic knowledge, skills and values. It has been observed that many of the students that went through universal basic education of 9-years programme are unable to read and perform basic calculations. The study therefore, want to examine the extent to which this assertion can be upheld in North-central, Nigeria. A descriptive survey design was adopted. The population comprised all students of Universal Basic 1 to 9 while the target population consisted of 645, 177 upper basic students in North-central, Nigeria. Researchers-developed numeracy manipulating test was constructed which contained thirty multiple-choice items. Scale content validity was computed and obtained 0.88 S-CVI. Kuder Richardson KR 20 was employed and obtained 0.81 reliability coefficient. Four research objectives were conceived. One research question was raised and answered using percentage. Three hypotheses were generated and tested using an independent t-test at 0.05 level of significance. One of the findings revealed that students possessed 41.61% numeracy skills. No significant difference existed based on gender. A significant difference existed based on school ownership and school location. It was concluded that the performance of students was weak and might inhibit national development. It was recommended that the governments at all levels should give more attention to the UBE programme being the foundation of other forms of education in Nigeria.